2014
DOI: 10.5114/pdia.2014.45070
|View full text |Cite
|
Sign up to set email alerts
|

The adherence and illness perception of patients diagnosed with asthma or chronic obstructive pulmonary disease treated with polytherapy using new generation Cyclohaler

Abstract: IntroductionThe factors influencing adherence of patients diagnosed with asthma and chronic obstructive pulmonary disease (COPD) include the complexity of the therapy, fear of side effects of drugs, method of taking the drug, dosage regimen, polypharmacy, adverse events, knowledge about the essence of the disease and its complications, illness perception and priorities in life, training on the use of the inhaler, the duration of treatment, social support, and drug availability.AimTo assess the adherence of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 17 publications
2
23
3
1
Order By: Relevance
“…In contrast to our study, non-adherent behaviours were associated with more negative perceived consequences of illness in a British study conducted among 100 asthma patients [14]. Furthermore, in a large Polish survey of 3618 asthma patients, illness perception, younger age, disease duration and severity were predictors of adherence to treatment with fluticasone propionate and formoterol fumarate [26]. It has also been suggested that interventions focusing on illness perception helped to support chronic obstructive pulmonary disease patients in their disease management and to improve health-related quality of life [27].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study, non-adherent behaviours were associated with more negative perceived consequences of illness in a British study conducted among 100 asthma patients [14]. Furthermore, in a large Polish survey of 3618 asthma patients, illness perception, younger age, disease duration and severity were predictors of adherence to treatment with fluticasone propionate and formoterol fumarate [26]. It has also been suggested that interventions focusing on illness perception helped to support chronic obstructive pulmonary disease patients in their disease management and to improve health-related quality of life [27].…”
Section: Discussioncontrasting
confidence: 99%
“…According to that model adherence to treatment consists of several components that the patient can adopt to cope with their disease. Only a few studies have assessed the association between illness perception and treatment adherence in asthma patients [14,26]. In contrast to our study, non-adherent behaviours were associated with more negative perceived consequences of illness in a British study conducted among 100 asthma patients [14].…”
Section: Discussioncontrasting
confidence: 97%
“…However, only a few addressed the WHO healthcare system dimension, particularly the access to pharmacy services. To address the patient-related dimension, we explored the patients' illness perception, which is thought to be a modifiable risk factor found to be significantly associated with medication adherence in other chronic diseases like diabetes, atrial fibrillation and chronic pulmonary diseases [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these factors are related to complexity of the therapy, fear of side effects of drugs, method of taking the drug, dosage regimen, adverse events, knowledge about the essence of the disease and its complications, illness perception and social support. 6 , 9 , 10 Especially, medical beliefs, cognitive and emotional perceptions have shown to be related to medical adherence. 11 , 12 Furthermore, individual asthma management might be improved by a better understanding of the types of beliefs or illness-related perceptions that are associated with low adherence to preventer medication.…”
Section: Introductionmentioning
confidence: 99%